Cerai Gugat dalam Putusan Pengadilan Agama Stabat Nomor 2119/ Pdt.G/ 2023/ PA. Stb.( Ditinjau dalam Perspektif Undang-Undang Nomor 23 Tahun 2004 tentang Penghapusan Kekerasan dalam Rumah Tangga dan Pasal 116 Kompilasi Hukum Islam) - Ahmad Habib Dairobi; Ali Akbar (Jurnal Ilmu Hukum, Humaniora dan Politik, 2024)
The panel of judges as representatives of the state has the authority and power to decide cases, whether to reject the divorce lawsuit or grant the divorce lawsuit. A divorce that occurs will certainly have legal consequences for husband and wife and children. Many divorce cases are not granted by the panel of judges, one of which is the Stabat Religious Court Decision Number 2119/ Pdt.G/ 2023/ PA. Stb. This research aims to further examine the judge's decision from the perspective of Law No. 23 of 2004 and the Compilation of Islamic Law. This research uses a statutory approach. The findings of this research are that the results of the lawsuit are rejected by arguing that the plaintiff and defendant's households have not entered the broken marriage stage, taking into account the length of the marriage period, the minimum period of separation between the plaintiff and the defendant, which in this consideration is contrary to Article 116 of the Compilation Islamic law, the divorce lawsuit is rejected.